Taking Risk: Early Results From Teaching Hospitals' Participation in the Center for Medicare and Medicaid Innovation Bundled Payments for Care Improvement Initiative. (July 2016) - Kivlahan, Coleen; Orlowski, Janis M.; Pearce, Jonathan; Walradt, Jessica; Baker, Matthew; Kirch, Darrell G.
Abstract : The authors describe observations from the 27 teaching hospitals constituting the Association of American Medical Colleges (AAMC) cohort in the Center for Medicare and Medicaid Innovation (CMMI) Bundled Payments for Care Improvement (BPCI) initiative. CMMI introduced BPCI in August 2011 and selected the first set of participants in January 2013. BPCI participants enter into Medicare payment arrangements for episodes of care for which they take financial risk. The first round of participants entered risk agreements on October 1, 2013 and January 1, 2014. In April 2014, CMMI selected additional participants who started taking financial risk in 2015. Selected episodes include congestive heart failure (CHF), major joint replacement (MJR), and cardiac valve surgery. The AAMC cohort of participating hospitals selected clinical conditions on the basis of patient volume, opportunity to impact savings and quality, organizational and clinical team readiness, and prior process improvement experience. Early financial results suggest that focused attention to postacute care utilization and outcomes, rapid changes in care processes, program pricing rules, and team composition drove savings and losses. The first cohort of participants generated savings in MJR, CHF, and cardiac valve episodes; losses were experienced in stroke, percutaneous coronary intervention, and spine surgery. Although about one-quarter of U.S. teaching hospitals are participating in BPCI, the proliferation of existing and new payment models, as well as the 2015 announcement to increasingly pay providers according to value, mandates close scrutiny of program outcomes. The authors conclude by proposing additional opportunities for research related to alternative payment models.